Location-Based Gaming Play in Public Space - Leorke, Dale (Springer Nature Singapore : Imprint: Palgrave Macmillan, 2019)
Location-based games emerged in the early 2000s following the commercialisation of GPS and artistic experimentation with 'locative media' technologies. Location-based games are played in everyday public spaces using GPS and networked, mobile technologies to track their players' location. This book traces the evolution of location-based gaming, from its emergence as a marginal practice to its recent popularisation through smartphone apps like Pokémon Go and its incorporation into 'smart city' strategies. Drawing on this history and an analysis of the scholarly and mainstream literature on location-based games, Leorke unpacks the key claims made about them. These claims position location-based games as alternately enriching or diminishing their players' engagement with the people and places they encounter through the game. Through rich case studies and interviews with location-based game designers and players, Leorke tests out and challenges these celebratory and pessimistic discourses. He argues for a more grounded approach to researching location-based games and their impact on public space that reflects the ideologies, lived experiences, and institutional imperatives that circulate around their design and performance. By situating location-based games within broader debates about the role of play and digitisation in public life, Location-Based Gaming offers an original and timely account of location-based gaming and its growing prominence.